Multiple Anomalies Of The Hand - Tripathi, Prof. F.M.; Atam, Dr. R.; Rai, Dr. A.K.; Gupta, Prof. S.K. (Indian Journal of Plastic Surgery, 1991)
Amongst all congenital anomaly, those of hands and lips are the commonest. Those of hands of minor degrees are seen very often, without they being corrected.A Study of 50 cases of congenital anomalies of hand show presence of multiple anomalies in 7 cases (14%). A detailed account of those cases is being presented.